Artificial Intelligence (AI) Enabled CRM Capabilities in the Era of Health Digitalization and Customer Satisfaction with the Serial Mediation of Customer Service Flexibility and Service Optimization - Sarwar, Humaira; Raza, Syed Ahsan; Saleem, Maria; Mahmood, Faisal (Business Review of Digital Revolution, 2024)
Artificial intelligence (AI) enabled customer relationship management (CRM) technologies are critical for increasing client satisfaction in the modern era of digitalization. They customize experiences, optimize processes, and offer predictive analytics for proactive service. Customers benefit from 24/7 support, which provides fast help. Data-driven insights boost strategy, whereas improved communication and scalability assure continuous service quality. Overall, AI CRM promotes strong customer interactions and long-term profitability. The objective of this research to investigate indispensable research question of what is the indirect impact of AI CRM on customer satisfaction with the mediation of customer service flexibility and service optimization by resource-based view theory. Philosophically, this research belongs post-positivist framework, with a deductive approach as the casual association among research variables are investigating by primary data through survey method by utilizing time-lagged design in the healthcare sector of Pakistan. The sample of this research is collected form purposefully selected 15 hospitals of different operating in three larger metropolitan cities of Punjab, Pakistan. This research utilized contemporary data utilized and analysis procedure. Data analysis is done by utilizing Smart PLS. This research found that AI CRM elevate the customer satisfaction with the mediation of customer service flexibility and service optimization. The association between AI CRM and company customer satisfaction is also examined. When contemplating the practical implications, managers and policymakers need to take into account the foundational structure to foster their customers.
Keywords: AI Enabled CRM; Health Digitalization; Customer Service Flexibility; Service Optimization; Customer Satisfaction